Leadership smarts inspiration and wisdom from the heart of a leader - Blanchard, Kenneth H. (David C. Cook, 2005)
Millions of people have improved their leadership and management style as well as the quality of their life after reading Ken Blanchard's best-selling books. Now, in Leadership Smarts, Blanchard reveals powerful life and leadership principles with simple insights that help you sharpen your leadership skills and build personal integrity. This book contains smart leadership advice on: aiming for excellence, maintaining integrity, finding courage to change, helping others reach their potential ...and much more.